Analysis of Dijkstra’s and A* algorithm to find the shortest path - Alija, Amani Saleh (2015)
There are so many algorithms used to find the shortest path such as Dijkstra, A* algorithm, Genetic algorithm, Floyd algorithm and Ant algorithm. In this study, two algorithms will be focused on. This study compares the Dijkstra’s, and A* algorithm to estimate search time and distance of algorithms to find the shortest path. It needs the appropriate algorithm to search the shortest path. Therefore, the purpose of this research is to explore which is the best shortest path algorithm by comparing the two types of algorithms. Such that it can be used to solve the problem path, search to analyze their efficiency in an environment based on two dimensional matrix which is best because of lookup time. This study implements the algorithm in visual C++ 2008 and design interface for the algorithms that allow the user to find the shortest path with the search time and the distance by determine the size of map, starting node and the destination node. The experimental result showed the search time of A* algorithm is faster than Dijkstra’s algorithm with average value 466ms and the distance is same of the both of algorithms.